Working memory processes and the histamine-3 receptor in schizophrenia: a [11C]MK-8278 PET-fMRI study - Atheeshaan Arumuham; Ekaterina Shatalina; Matthew M. Nour; Mattia Veronese; Ellis Chika Onwordi; Stephen J. Kaar; Sameer Jauhar; Eugenii A. Rabiner; Oliver D. Howes (Psychopharmacology, 2025)
Rationale Working memory impairment is a prominent feature of schizophrenia which predicts clinical and functional outcomes. Preclinical data suggest histamine-3 receptor (H3R) expression in cortical pyramidal neurons may have a role in working memory, and post-mortem data has found disruptions of H3R expression in schizophrenia. Objectives We examined the role of H3R in vivo to elucidate its role on working memory impairment in schizophrenia. Methods We used positron emission tomography (PET) with the selective H3R radioligand [ 11 C]MK-8278 to measure H3R availability, and employed a task during functional magnetic resonance imaging (fMRI) to assess working memory-evoked brain activation and cognitive task performance, in patients with schizophrenia ( n = 12) and matched healthy volunteers ( n = 12). We assessed the relationship between H3R availability and both task performance and working memory-evoked brain activation in regions of interest (ROIs), including the anterior cingulate cortex (ACC) and dorsolateral prefrontal cortex (DLPFC). Results Patients with schizophrenia showed a strong positive correlation, after corrections for multiple comparisons, between ACC H3R availability and task performance (rho = 0.73, p = 0.007), which was absent in the control group (rho = 0.03, p = 0.94). Further ROI analysis did not find a significant relationship between H3R availability and working memory-evoked brain activation. Conclusions These results provide support for the role of H3R on working memory processes in patients with schizophrenia.

The effects of AUT00206, a novel Kv3.1/3.2 potassium channel modulator, on task-based reward system activation: a test of mechanism in schizophrenia - Stephen J. Kaar; Ilinca Angelescu; Matthew M. Nour; Tiago Reis Marques; Alice Sharman; Anil Sajjala; John Hutchison; Philip McGuire; Charles Large; Oliver D. Howes (Psychopharmacology, 2022)
The pathophysiology of schizophrenia involves abnormal reward processing, thought to be due to disrupted striatal and dopaminergic function. Consistent with this hypothesis, functional magnetic resonance imaging (fMRI) studies using the monetary incentive delay (MID) task report hypoactivation in the striatum during reward anticipation in schizophrenia. Dopamine neuron activity is modulated by striatal GABAergic interneurons. GABAergic interneuron firing rates, in turn, are related to conductances in voltage-gated potassium 3.1 (Kv3.1) and 3.2 (Kv3.2) channels, suggesting that targeting Kv3.1/3.2 could augment striatal function during reward processing. Here, we studied the effect of a novel potassium Kv3.1/3.2 channel modulator, AUT00206, on striatal activation in patients with schizophrenia, using the MID task. Each participant completed the MID during fMRI scanning on two occasions: once at baseline, and again following either 4 weeks of AUT00206 or placebo treatment. We found a significant inverse relationship at baseline between symptom severity and reward anticipation-related neural activation in the right associative striatum ( r = -0.461, p = 0.035). Following treatment with AUT00206, there was a significant increase in reward anticipation-related activation in the left associative striatum (t (13) = 4.23, peak-level p (FWE) < 0.05)), but no significant effect in the ventral striatum. This provides preliminary evidence that the Kv3.1/3.2 potassium channel modulator, AUT00206, may address reward-related striatal abnormalities in schizophrenia.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The acute effects of cannabidiol on emotional processing and anxiety: a neurocognitive imaging study - Michael A. P. Bloomfield; Yumeya Yamamori; Chandni Hindocha; Augustus P. M. Jones; Jocelyn L. L. Yim; Hannah R. Walker; Ben Statton; Matthew B. Wall; Rachel H. Lees; Oliver D. Howes; Valerie H. Curran; Jonathan P. Roiser; et al. (Psychopharmacology, 2022)
Rationale There is growing interest in the therapeutic potential of cannabidiol (CBD) across a range of psychiatric disorders. CBD has been found to reduce anxiety during experimentally induced stress in anxious individuals and healthy controls. However, the mechanisms underlying the putative anxiolytic effects of CBD are unknown. Objectives We sought to investigate the behavioural and neural effects of a single dose of CBD vs. placebo on a range of emotion-related measures to test cognitive-mechanistic models of its effects on anxiety. Methods We conducted a randomised, double-blind, placebo-controlled, crossover, acute oral challenge of 600 mg of CBD in 24 healthy participants on emotional processing, with neuroimaging (viewing emotional faces during functional magnetic resonance imaging) and cognitive (emotional appraisal) measures as well as subjective response to experimentally induced anxiety. Results CBD did not produce effects on brain responses to emotional faces and cognitive measures of emotional processing, or modulate experimentally induced anxiety, relative to placebo. Conclusions Given the rising popularity of CBD for its putative medical benefits, these findings question whether further research is warranted to investigate the clinical potential of CBD for the treatment of anxiety disorders.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Historic and Modern Approaches for the Discovery of Abandoned Wells for Methane Emissions Mitigation in Oil Creek State Park, Pennsylvania - Patricia M. B. Saint-Vincent; James I. Sams; Mumbi Mundia-Howe; Matthew D. Reeder; Garret A. Veloski; Natalie J. Pekney (Environmental Management, 2021)

Leveraging a Landscape-Level Monitoring and Assessment Program for Developing Resilient Shorelines throughout the Laurentian Great Lakes - Donald G. Uzarski; Douglas A. Wilcox; Valerie J. Brady; Matthew J. Cooper; Dennis A. Albert; Jan J. H. Ciborowski; Nicholas P. Danz; Anne Garwood; Joseph P. Gathman; Thomas M. Gehring; Greg P. Grabas; Robert W. Howe; et al. (Wetlands, 2019)

Transforming growth factor-β promotes basement membrane fibrosis, alters perivascular cerebrospinal fluid distribution, and worsens neurological recovery in the aged brain after stroke - Matthew D. Howe; J. Weldon Furr; Yashasvee Munshi; Meaghan A. Roy-O’Reilly; Michael E. Maniskas; Edward C. Koellhoffer; John d’Aigle; Lauren H. Sansing; Louise D. McCullough; Akihiko Urayama (GeroScience, 2019)

Standardized Measures of Coastal Wetland Condition: Implementation at a Laurentian Great Lakes Basin-Wide Scale - Donald G. Uzarski; Valerie J. Brady; Matthew J. Cooper; Douglas A. Wilcox; Dennis A. Albert; Richard P. Axler; Peg Bostwick; Terry N. Brown; Jan J. H. Ciborowski; Nicholas P. Danz; Joseph P. Gathman; Thomas M. Gehring; et al. (Wetlands, 2017)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)